(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
Correlation between Lower Kimmeridgian marly Lacunosamergel Formation of Swabia and the limestone-dominated Arzberg Formation of Franconia was recently carried out successfully. Correlation difficulties in the past were encountered in the Hypselocyclum Zone and in the Divisum Zone ("Balderum-Bank"). Base and top of the Hypselocyclum Zone, sensu Atrops: the Hippolytense Subzone and Perayensis horizon respectively, were correlated with numerous finds of Cymaceras guembeli (Oppel) on the base, and Ardescia perayensis Atrops on the top throughout Franconia and Swabia. For the first time several Aspidoceras (Pseudhimalayites) uhlandi (Oppel) were found in the Swabian Alb above the "Balderum-Bank". These finds help to correct misinterpretations based on the presumed limited vertical range of A. uhlandi in Swabia and the lack of finds of Idoceras balderum (Oppel) in some sections of S Franconia. Now, the widened range of Aspidoceras (P.) uhlandi allows long-distance correlation with the Western Mediterranean Domain sensu Olóriz.